ACE Aktivitas Inhibitor Angiotension Converting Enzyme (ACE) Fraksi Protein Susu Kerbau (Bubalus bubalis) Fermentasi - Sri Yadial Chalid; Siti Nurbayati; Andhika Fajar Pratama (Fakultas Farmasi Universitas Pancasila, 2018)
Proteins and peptides are food components that have proven ability to prevent hypertensive disease through inhibition of angiotensin converting enzyme (ACE). Buffalo milk or fermented curds are naturally potentially developed as functional food as antihypertensive food. The purpose of this study were to determine the optimum fermentation time to obtain curd with the best ACE inhibition activity. First the curd protein was extracted using alcohol in stages for curd with fermentation length of 1, 2, 3, and 4 days. Nol days or buffallo milk without fermentation as control. Every time fermentation variation of were tested pH acidity level, chemical composition, protein extraction, dissolved protein content, degree of hydrolysis and ACE inhibitor activity. The value ACE inhibitor the highest was done fractionate using ultrafiltration membranes helping centrifugation. The protein fraction with optimal ACE inhibitor activity was analyzed amino acid composition by ultra performance liquid chromatography. The result of research are time fermentaion is one day and dissolved protein content is 912,73 ppm. The highest ACE inhibition activity was obtained at 87.52%, and 23.38% for degree of hydrolysis. Based on molecular weight was obtained the highest ACE inhibition value at fraction below 3 kDa, the ACE inhibitor activity value is 99,3%. Amino acid composition are threonine 0,0249%, proline 0,039%, alanine 0,045%, phenyl alanine smaller than 0,012% and acid glutamate 0.158%. In general, dadih was able to inhibit ACE activity and potentially as an antihypertensive agent in vitro.